Hidden Debt : Solutions to Avert the Next Financial Crisis in South Asia - Melecky, Martin (Washington, DC: World Bank, 2021)
The COVID-19 crisis, which has sent economies in South Asia and around the world into a deep recession, has highlighted South Asia’s rising debt levels and sizable hidden liabilities. State-owned enterprises, state-owned commercial banks, and public-private partnerships have been at the center of the rising debt wave and the latest pandemic response. Historically, South Asia has relied on these direct public interventions more than other regions. The interventions have helped governments tackle key development challenges and rapidly deliver relief measures during crises. However, because of their inefficiencies and weak governance, the interventions are also a significant source of public indebtedness and macrofinancial risks. Hidden Debt examines the trade-off between tackling development challenges through direct state presence in the market and avoiding unsustainable debt due to economic inefficiencies of such off–balance sheet operations, which greatly leverage public capital. The study recommends a reform agenda based on the four interrelated principles of purpose, incentives, transparency, and accountability (PITA). The reforms can mitigate the risks that off–balance sheet operations will become the source of the next financial crisis in South Asia.